Play as a Stress-Coping Method Among Children in Light of the COVID-19 Pandemic: A Review - Raudenská, Jaroslava; Gumančík, Jiří; Raudenský, Martin; Pasqualucci, Alberto; Narvaez Tamayo, Marco Antonio; Varrassi, Giustino; Javůrková, Alena (Curēus, 2023)
The COVID-19 pandemic, which started in early 2020, has been a great source of stress for almost every person all around the world. However, this is particularly true for children. It is necessary to fully address the stress-related psychosocial issues connected with the pandemic, solely in children. Play is important for children's development, as it is a natural activity for every child. Through play and play-based interventions, children can communicate non-verbally, symbolically, and in an action-oriented manner. Therefore, play-based interventions may have the potential to be one of the coping strategies used by children who experience stress, especially during the COVID-19 pandemic. The aim of this narrative review was to show how play-based activities could help children deal with stress related to the COVID-19 pandemic in the non-clinical population. A systematic search of the literature in various databases was performed. The initial search provided 5,004 potentially eligible studies in various databases, and 42,201 records identified from Google Scholar. After excluding studies not meeting the inclusive criteria, nine papers were selected for this narrative review. This narrative review showed findings that play-based activities can have a positive effect during the COVID-19 pandemic on different stress levels in the children population. Additionally, the findings of this review highlight the importance of further research and implementation of play into many aspects of children's life.